Perceptions, barriers and enablers of salt reduction in Malaysian out-of-home sectors (MySaltOH): from the point of view of policy-makers and food industries - Zaliha, Harun; Suzana, Shahar; You, Yee Xing; Zahara Abdul, Manaf; Hazreen Abdul, Majid; Chia, Yook Chin *; Hasnah, Haron; Michael, Viola; Noor Shahida, Sukiman; Aida Farzana, Mohamad Taib; He, Feng J; Brown, Mhairi Karen (BMC, 2023)
Background: High salt intake is a major cause of hypertension and cardiovascular diseases. The out-of-home sectors have been identified as one of the contributors of high salt intake in the population. The National Salt Reduction Policy of Malaysia was initiated in 2015; however, out-of-home sectors are yet to be emphasized and perception by policy-makers and the food industries towards salt reduction are yet unknown. This study aimed to determine the perceptions, barriers and enablers towards salt reduction in the out-of-home sector in Malaysia, as well as among policy-makers and the food industries.